Sistem Pemantauan dan Kendali Kelembapan Udara Pada Budi Daya Bunga Anggrek Berbasis Internet of Things - Siti Aminah; Tedy Rismawan; Suhardi Suhardi; Dedi Triyanto (STMIK Budi Darma, 2022)
Orchid cultivation has been widely carried out by orchid agribusiness in Indonesia, even though there has been a lot of orchid cultivation but there are still obstacles in terms of supplies or maintenance. One of them is water sprinkling and fertilizing the orchid plants which are still done manually. Manual watering is watering done by orchid farmers so it requires a lot of effort and time and the amount of water that is sprinkled is not the same. If the water is poured too much or too little, it can cause rot or dryness of the plant roots so that the plants can die quickly. In the current technological era, watering can be done automatically by utilizing Internet of Things (IoT) technology and implementing the Wireless Sensor Network (WSN) system. NodeMCU ESP32 is used to control all hardware and software components. In this system there are 2 sensor nodes and 1 controller node. Users can control manually or automatically through the website interface. From the results of the implementation and testing it can be concluded that the system is able to provide information on conditions of temperature, air humidity, humidity of the planting medium, water level, liquid fertilizer height and water pH. The system is also capable of running automatic and manual systems, namely controlling and providing on/off condition information on water pumps, fertilizer pumps, faucet 1, faucet 2, faucet 3, fan 1, fan 2 and fan 3 on the website. The effect of the automatic system on the orchid plants was very good, because on the 41st day, the orchid plants using the automatic system experienced faster growth of new shoots, compared to using the manual system. The average delay time for the entire system is 4.5 seconds.